The POWHER School: Transforming Care Provided by Guatemalan Traditional Birth Attendants. Issue 5 (September 2019) - Callister, Lynn Clark
Abstract : Our global health and nursing expert, Dr. Callister, discusses the School of POWHER (Providing Outreach in Women's Health and Educational Resources) that was founded in Sololá in the western highlands of Guatemala in 2011 to help train traditional birth attendants for safe maternity care. Respect for culture and local customs are important aspects of this successful program.